De la transmission à la construction des savoirs et des pratiques dans les relations intergénérationnelles de femmes réfugiées au Québec - Vatz Laaroussi, Michèle; Guilbert, Lucille; Rachédi, Lilyane; Kanouté, Fasal; Ansòn, Laura; Canales, Tania; León Correal, Amelia; Presseau, Ariane; Thiaw, Marie Louise; Zivanovic Sarenac, Javorka (Nouvelles pratiques sociales, 2012)
Parler de familles immigrantes en intervention sociale, c’est souvent parler des problèmes intergénérationnels et des difficultés d’intégration. À partir d’une recherche menée auprès de trios de femmes réfugiées au Québec (des grands-mères, des mères et des filles), ce texte s’intéresse aux processus originaux de circulation des savoirs et de construction de nouvelles pratiques entre ces générations de femmes. Leurs rapports à l’autonomie, mais aussi à la famille, au travail, à la santé ou à la collectivité se transforment et se modulent différemment selon les générations et les événements de leur trajectoire. Ces échanges intergénérationnels sont importants pour l’insertion des divers membres des familles immigrantes et il est nécessaire que les intervenants en aient une compréhension renouvelée.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; construction du savoir; cours; discipline; discours dominant; famille; féminisme décolonial; immigration; inégalités; premier cycle; pédagogie; périodes historiques; québec; régions géographiques; santé; savoirs; sciences humaines; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; transmissions; travail

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children--The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis